Boreal permafrost thaw amplified by fire disturbance and precipitation increases. (18th November 2020) - Williams, Mathew; Zhang, Yu; Estop-Aragonés, Cristian; Fisher, James P; Xenakis, Georgios; Charman, Dan J; Hartley, Iain P; Murton, Julian B; Phoenix, Gareth K
Abstract: Permafrost soils store huge amounts of organic carbon, which could be released if climate change promotes thaw. Currently, modelling studies predict that thaw in boreal regions is mainly sensitive to warming, rather than changes in precipitation or vegetation cover. We evaluate this conclusion for North American boreal forests using a detailed process-based model parameterised and validated on field measurements. We show that soil thermal regimes for dominant forest types are controlled strongly by soil moisture and thus the balance between evapotranspiration and precipitation. Under dense canopy cover, high evapotranspiration means a 30% increase in precipitation causes less thaw than a 1 °C increase in temperature. However, disturbance to vegetation promotes greater thaw through reduced evapotranspiration, which results in wetter, more thermally conductive soils. In such disturbed forests, increases in precipitation rival warming as a direct driver of thaw, with a 30% increase in precipitation at current temperatures causing more thaw than 2 °C of warming. We find striking non-linear interactive effects on thaw between rising precipitation and loss of leaf area, which are of concern given projections of greater precipitation and disturbance in boreal forests. Inclusion of robust vegetation-hydrological feedbacks in global models is therefore critical for accurately predicting permafrost dynamics; thaw cannot be considered to be controlled solely by rising temperatures.